Multimodal secondary prevention behavioral interventions for TIA and stroke: a systematic review and meta-analysis. - Maggie Lawrence; Jan Pringle; Susan Kerr; Joanne Booth; Lindsay Govan; Nicola J Roberts (PLoS ONE)
Background Guidelines recommend implementation of multimodal interventions to help prevent recurrent TIA/stroke. We undertook a systematic review to assess the effectiveness of behavioral secondary prevention interventions. Strategy Searches were conducted in 14 databases, including MEDLINE (1980-January 2014). We included randomized controlled trials (RCTs) testing multimodal interventions against usual care/modified usual care. All review processes were conducted in accordance with Cochrane guidelines. Results Twenty-three papers reporting 20 RCTs (6,373 participants) of a range of multimodal behavioral interventions were included. Methodological quality was generally low. Meta-analyses were possible for physiological, lifestyle, psychosocial and mortality/recurrence outcomes. Note: all reported confidence intervals are 95%. Systolic blood pressure was reduced by 4.21 mmHg (mean) (-6.24 to -2.18, P = 0.01 I2 = 58%, 1,407 participants); diastolic blood pressure by 2.03 mmHg (mean) (-3.19 to -0.87, P = 0.004, I2 = 52%, 1,407 participants). No significant changes were found for HDL, LDL, total cholesterol, fasting blood glucose, high sensitivity-CR, BMI, weight or waist:hip ratio, although there was a significant reduction in waist circumference (-6.69 cm, -11.44 to -1.93, P = 0.006, I2 = 0%, 96 participants). There was no significant difference in smoking continuance, or improved fruit and vegetable consumption. There was a significant difference in compliance with antithrombotic medication (OR 1.45, 1.21 to 1.75, P<0.0001, I2 = 0%, 2,792 participants) and with statins (OR 2.53, 2.15 to 2.97, P< 0.00001, I2 = 0%, 2,636 participants); however, there was no significant difference in compliance with antihypertensives. There was a significant reduction in anxiety (-1.20, -1.77 to -0.63, P<0.0001, I2 = 85%, 143 participants). Although there was no significant difference in odds of death or recurrent TIA/stroke, there was a significant reduction in the odds of cardiac events (OR 0.38, 0.16 to 0.88, P = 0.02, I2 = 0%, 4,053 participants). Conclusions There are benefits to be derived from multimodal secondary prevention interventions. However, the findings are complex and should be interpreted with caution. Further, high quality trials providing comprehensive detail of interventions and outcomes, are required. Review registration PROSPERO CRD42012002538.